1981
DOI: 10.1159/000128181
|View full text |Cite
|
Sign up to set email alerts
|

Clotting and Other Plasma Factors in Experimental Endotoxemia: Inhibition of Degradation by Exogenous Proteinase Inhibitors

Abstract: Endotoxemia in dogs was induced by a slow intravenous infusion of E. coli endotoxin for 2 h. Thereby, a significant decrease was observed in the plasma levels of several clotting, fibrinolysis and complement factors. The changes were studied over an experimental period of 14 h and checked for statistical significance by three-way analysis of variance. Application of the broad-spectrum proteinase inhibitor aprotinin (Trasylol®) from bovine organs clearly lowered the endotoxin-induced decline of the plasma prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 18 publications
0
15
0
4
Order By: Relevance
“…Infusion of endotoxin (lipopolysaccharide [LPS]) into animals has been shown to cause an activation of the coagulation cascade and to cause acute lung injury characterized by pulmonary hypertension, pulmonary endothelial injury, increased pulmonary vascular permeability, and pulmonary edema (4)(5)(6)(7)(8). Serine proteases, such as thrombin, plasmin, or plasma kallikrein, generated during activation of the coagulation cascade have been shown to activate polymorphonuclear leukocytes (PMN) as well as to directly increase pulmonary vascular permeability (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of endotoxin (lipopolysaccharide [LPS]) into animals has been shown to cause an activation of the coagulation cascade and to cause acute lung injury characterized by pulmonary hypertension, pulmonary endothelial injury, increased pulmonary vascular permeability, and pulmonary edema (4)(5)(6)(7)(8). Serine proteases, such as thrombin, plasmin, or plasma kallikrein, generated during activation of the coagulation cascade have been shown to activate polymorphonuclear leukocytes (PMN) as well as to directly increase pulmonary vascular permeability (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Elastase is released into the circulation in acute leukemia and in septicemia (4). Several studies have indicated that the decrease in the concentration of coagulation factors seen in these conditions may be the result of direct proteolysis by leukocyte elastase (5). Leukocyte elastase also inactivates human antithrombin III (6), a2-plasmin inhibitor, and C1 inactivator (7).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are data suggest ing that aprotinin may restrain the traumatic or septic activation of the various 'cascades' including the coagulation and complement systems in the circulation of the patient [10,16]. This raises the question whether apro tinin added to blood units may not exert its principal effects on events occurring in the recipient at the time of the transfusion, rather than as a stabilizer during a storage period.…”
mentioning
confidence: 99%